Thin film with composition gradient inorganic layer, method for manufacturing the same and display device
By adjusting the oxygen and carbon content ratio in the SiOxCy film of carbon oxide, forming a component gradient structure, the problems of scratch resistance and transparency of the SiOx film are solved, and better folding durability and optical performance are achieved. Protective film suitable for foldable display devices.
Patent Information
- Application Number
- CN202211292239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-27
- Filing Date
- 2022-10-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-10-20
AI Technical Summary
The existing SiOx film lacks scratch resistance, while the SiCy film has poor transparency, and the combined film is prone to peeling between layers when folded, which fails to fully utilize the advantages of both.
By adjusting the oxygen content ratio and carbon content ratio in the thickness direction of the SiOxCy film of silicon oxide, a component gradient structure is formed, adhesion and transparency are improved, and the reaction gas injection amount is adjusted through the roll-to-roll plasma sputtering process, and the preparation is made Protective film with the advantages of SiOx and SiCy films.
It achieves better folding durability, scratch resistance and optical properties, enhances the scratch resistance and transparency of the film, and reduces the risk of interlayer peeling, and is suitable for the protective film of foldable display devices.
Smart Images

Figure CN116023697B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a film with a composition gradient inorganic layer, a preparation method thereof and a display device. Background Art
[0002] With the demands brought by the development of IT equipment, display technology is constantly developing, and technologies such as curved display and ventilation display have entered the commercialization process. Recently, in the field of mobile devices that require both large screens and portability, flexible display devices that can be flexibly bent or folded according to external forces are preferred. In particular, the biggest advantage of foldable display devices is that they can be folded and reduced when not in use to increase portability, and when in use, they can be unfolded to achieve a large screen.
[0003] Transparent polyimide film or ultra-thin glass (UTG) is applied to the window of flexible display device, but there are still some problems. Transparent polyimide film is easily affected by external scratches and lacks barrier properties to moisture or oxygen, while ultra-thin glass has weak shatterproof properties. Therefore, inorganic thin films with good scratch resistance and moisture permeability resistance, such as protective films of metal oxides or metal nitrides, are now applied to the window surface. In addition, in recent years, in order to prevent external light from being reflected on the front surface of the display and causing a decrease in visibility, surface treatment technology is being developed to reduce the reflectivity of the film applied to the front surface of the display device.
[0004] For example, Japanese Patent Publication No. 2003-098306 discloses a film having an anti-reflection effect by alternately stacking silicon oxide layers and indium tin oxide layers on its surface, and at the same time imparting scratch resistance by depositing a dense carbon-based film on its surface. However, the problem is that the film must be made by depositing a carbon-based film alone to improve scratch resistance, which is too cumbersome and reduces transparency.
[0005] [References]
[0006] (Patent Document 1) Japanese Laid-Open Patent Publication No. 2003-098306. Summary of the invention
[0007] Problems to be solved by the invention
[0008] Currently developing SiOx thin films with excellent adhesion to substrates and transparency, or SiC with high scratch resistance y The film is suitable for the protective film of the window of the foldable display device, but there is still SiO x The film lacks scratch resistance and SiC y The disadvantage of poor film transparency.
[0009] In order to solve this technical problem, we are trying to combine SiO x Thin Film and SiC yThin film or SiO with appropriately adjusted carbon-oxygen ratio x C y However, as the number of films increases, the possibility of interlayer delamination during folding will also increase. x C y The film failed to fully utilize SiO x Thin Film and SiC y Advantages of thin films.
[0010] To address this problem, the present invention achieves effective provision of SiO by adjusting different carbon-oxygen ratios in the thickness direction. x Thin Film and SiC y In addition, by applying a roll-to-roll method to a deposition process such as reactive plasma sputtering, the film can be efficiently prepared by adjusting different reactive gas injection amounts at the front and back ends.
[0011] Therefore, the present invention provides a film that can be used to protect the window of a folding display device, a method for manufacturing the film, and a display device comprising the film, which has excellent optical properties, scratch resistance, and foldability.
[0012] Technical means to solve the problem
[0013] According to one embodiment, the present invention provides a thin film, comprising a base layer and a first inorganic layer, wherein the first inorganic layer is arranged on one side surface of the base layer; wherein the first inorganic layer comprises silicon oxycarbide SiO x C y , and the oxygen content ratio and carbon content ratio change in the thickness direction.
[0014] According to another embodiment, the present invention provides a method for preparing a thin film, comprising the step of depositing the first inorganic layer on one side surface of a substrate layer, wherein the first inorganic layer comprises silicon oxycarbide SiO x C y ; In the first inorganic layer, the oxygen content ratio and the carbon content ratio are changed in the thickness direction.
[0015] According to another embodiment, the present invention provides a display device including the embodiment, which includes a display panel; a window arranged on the front surface of the display panel; and a protective film arranged on the surface of the window; wherein the protective film includes the thin film in the embodiment.
[0016] Effects of the Invention
[0017] The thin film according to the embodiment is formed by including the silicon oxycarbide SiO x C y The thickness direction of the inorganic layer can adjust the different oxygen content ratios and carbon content ratios, effectively providing SiOx Thin Film and SiC y The advantage of the film is that it has better folding durability than the traditional film that combines the two films.
[0018] Specifically, by increasing the amount of silicon oxide SiO x C y The oxygen content ratio of the inorganic layer on both sides of the substrate bonding surface is increased, and the carbon content ratio is increased on the other side, thereby improving the adhesion to the substrate and transparency while giving the surface scratch resistance, and the inorganic layer can be implemented as a single layer. In addition, an anti-reflection function can also be provided by a laminated structure, which is composed of the inorganic layer and other layers with different refractive indices.
[0019] In particular, the thin film of the above-mentioned embodiment can be effectively prepared by applying the roll-to-roll method to a deposition process such as reactive plasma sputtering, and adjusting different injection amounts of reactive gases at the front end and the back end.
[0020] Therefore, the film of the above embodiment can be applied to a protective film for various products such as foldable display devices that need to have optical properties, outdoor visibility, scratch resistance and foldability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A cross section of a film of one embodiment is shown.
[0022] Figure 2 A cross section of a film of another embodiment is shown.
[0023] Figure 3 A thin film preparation method according to an embodiment is shown.
[0024] Figure 4 Another embodiment of a thin film preparation method is shown.
[0025] Figure 5 SIMS results showing the depth of the inorganic layer of a thin film according to an embodiment.
[0026] Figure 6 An example of a folding test showing a film sample.
[0027] Figure 7 An exploded perspective view showing a display device according to an embodiment.
[0028] Figure 8a and 8b Flexible display devices of external folding and internal folding types are shown respectively.
[0029] Description of Reference Numerals
[0030] 1: display device, 1a: inner foldable flexible display device, 1b: outer foldable flexible display device, 3: folding tester, 10: (protective) film, 10a: film sample, 20: window, 30: display panel, 100: base layer, 201: particles with high oxygen ratio, 202: particles with high carbon ratio, 210: first inorganic layer, 211: first surface, 212: second surface, 220: second inorganic layer 300: target material, 310: first target material, 320: second target material, 330: third target material, 340: fourth target material, 350: fifth target material, 401: first nozzle, 402: second nozzle, 501: discharge gas, 502: reaction gas, 600: plasma, 710: roller, 720: unwinding roller, 730: winding roller, T: thickness of the first inorganic layer, p1, p2: folding point. DETAILED DESCRIPTION
[0031] Various embodiments will be described in detail below with reference to the accompanying drawings.
[0032] When describing the embodiments, if it is determined that the specific description of the related known structure or function may obscure the key points of the embodiments, the detailed description thereof is omitted. In addition, the size of each structural element in the figure may be exaggerated or omitted for illustrative purposes and may be different from the size of actual application.
[0033] In this article, a structural element is described as being formed above / below other structural elements, or being connected or combined with each other, including being formed directly or indirectly formed, connected or combined between other structural elements. It should also be understood that the upper / lower reference of each structural element may vary depending on the direction of observing the object.
[0034] The terms used to refer to each structural element here are used to distinguish it from other structural elements and are not used to limit the embodiments. In addition, unless otherwise specified, the singular here refers to the plural expression that is not clearly referred to in the context.
[0035] In this document, the terms first, second, etc. are used to describe various structural elements, and the above structural elements should not be limited by the above terms. The terms are used to distinguish one structural element from another structural element.
[0036] The term “comprising” in this specification is intended to specify certain properties, regions, steps, procedures, elements and / or components, and does not exclude the existence or addition of other properties, regions, steps, procedures, elements and / or components unless otherwise stated.
[0037] Thin films with compositionally graded inorganic layers
[0038] Figure 1 FIG. 4 is a cross section of a film according to an embodiment.
[0039] refer to Figure 1 According to an embodiment, a thin film 10 includes a base layer 100 ; and a first inorganic layer 210 , wherein the first inorganic layer is disposed on one side surface of the base layer 100 .
[0040] The thin film may include one or more of the first inorganic layers.
[0041] The first inorganic layer is formed on one side surface of the base layer and includes silicon oxycarbide SiO x C y .
[0042] In the carbon oxide SiO x C y In the embodiment, the silicon Si atom may have a network structure of continuously bonding carbon C and oxygen O atoms. Therefore, the first inorganic layer may have the properties of a glass material. In addition, the first inorganic layer may have a polycrystalline or amorphous structure.
[0043] The silicon oxide SiO x C y The composition of can be measured by various methods, for example, by secondary ion mass spectrometry SIMS. Wherein, x and y are the relative atomic ratios of oxygen O and carbon C to silicon Si, respectively, and refer to the atomic number ratio or atomic molar ratio.
[0044] For example, silicon oxycarbide SiO x C y The atomic ratio x of oxygen to silicon in the first inorganic layer may be 0 to 2, and the atomic ratio y of carbon to silicon may be 0 to 1. x C y In the above, the relationship x=2(1-y) may be theoretically possible, but there is no particular limitation on this. That is, the actual analysis results may differ from the theoretical values, for example, x and y may differ from the theoretical values within a range of ±15%, specifically within ±10%, and more specifically within ±5%.
[0045] refer to Figure 1 , the oxygen content ratio and the carbon content ratio of the first inorganic layer 210 vary in the thickness T direction. The thin film according to the embodiment comprises the silicon oxide SiO x C y The thickness direction of the first inorganic layer is adjusted to have different oxygen content ratios and carbon content ratios, effectively providing SiO x Thin Film and SiC y The advantage of the film is that the folding durability is superior compared to conventional films that combine the two films.
[0046] refer to Figure 1The first inorganic layer 210 has a first surface 211 facing the base layer 100 and a second surface 212 opposite to the first surface 211; according to an embodiment, the silicon oxycarbide SiO x C y In the first inorganic layer, the oxygen O content ratio may gradually decrease and the carbon C content ratio may gradually increase from the first surface to the second surface.
[0047] Therefore, the oxygen content ratio of the first surface may be higher than that of the second surface, while the carbon content ratio may be lower. Specifically, the oxygen content ratio of the first surface in the first inorganic layer is the highest, and the carbon content ratio is the lowest. Therefore, the first surface may have the same x In addition, the carbon content ratio of the second surface may be higher than that of the first surface, while the oxygen content ratio may be lower. Specifically, the carbon content ratio of the second surface in the first inorganic layer is the highest, and the oxygen content ratio is the lowest. Therefore, the second surface may have the same properties as SiO y Similar properties.
[0048] On the first surface of the silicon oxide SiO x C y The atomic ratio x of oxygen to silicon in the first surface may be, for example, greater than 1.0, greater than 1.3, greater than 1.5, or greater than 1.6, and may also be less than 2.0, less than 1.9, less than 1.8, or less than 1.7. x C y The atomic ratio y of carbon to silicon may be, for example, 0 or more, more than 0, 0.01 or more, 0.1 or more, or 0.2 or more, and may also be 0.5 or less, 0.4 or less, or 0.3 or less.
[0049] The silicon oxide carbide SiO x C y The atomic ratio x of oxygen to silicon in the second surface may be, for example, greater than 0, greater than 0.01, greater than 0.05, or greater than 0.07, and may also be less than 0.5, less than 0.3, less than 0.2, or less than 0.1. x C y The atomic ratio y of carbon to silicon may be, for example, 0.5 or more, 0.6 or more, 0.7 or more, or 0.8 or more, and may also be 1 or less, less than or equal to 1, 0.95 or less, or 0.9 or less.
[0050] For example, the first surface of the silicon oxycarbide SiO x C y In the embodiment, the atomic ratio x:y of oxygen O:carbon C can be 1.5-1.9:0.1-0.5, and the carbon oxide SiOx C y In the above, the atomic ratio x:y of oxygen O:carbon C can be 0.05-0.1:0.8-0.9. The atomic ratio refers to the ratio of the number of atoms, and can also be interpreted as the meaning of atomic molar ratio.
[0051] For example, the first surface of the silicon oxycarbide SiO x C y The atomic ratio of Si:O:C in the second surface can be 1:1.5-1.9:0.1-0.5, and the silicon oxide SiO x C y The atomic ratio of Si:O:C can be 1:0.05~0.1:0.8~0.9.
[0052] Therefore, since the oxygen content ratio of the first surface (the bonding surface with the base layer) of the thin film inorganic layer is high, the adhesion with the base layer can be improved to increase the folding durability and transparency, and since the carbon content ratio of the second surface (outer surface) is high, the surface can be given scratch resistance, and these two characteristics can be achieved in a single layer respectively.
[0053] Figure 5 The SIMS results of the depth of the first inorganic layer of the thin film according to one embodiment are shown. Figure 5 As shown, the first inorganic layer in the thin film according to an embodiment has a composition gradient, wherein the ratio x of oxygen O and the ratio y of carbon C gradually increase or decrease in the thickness direction; specifically, as the depth ( Figure 5 The increase in the x-axis value in the graph is related to the carbon molar content ( Figure 5 The change in the y-axis value of the solid line curve) and the molar content of oxygen ( Figure 5 The change in the y-axis value of the dashed line curve is approximately 2 times.
[0054] In the first inorganic layer of the thin film, there is a point where the increase and decrease change is intermediate (i.e., a point where the atomic ratio of oxygen to carbon (x / y) reaches about 2) (at Figure 5 The point where the two curves intersect is represented by T1), and the depth of this point (relative to the percentage of the thickness of the first inorganic layer) can be defined as Txy in the following formula. Txy defined in the following formula can be, for example, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, or more than 50%, and can also be less than 80%, less than 75%, less than 70%, less than 65%, less than 60%, less than 55%, or less than 50%. For example, Txy defined by the following formula can be between 30% and 70%. Specifically, Txy defined in the following formula can be 40% to 60%.
[0055] Txy(%)=[(T0-T1) / T0]×100
[0056] Among them, T0 is the thickness of the first inorganic layer, in nm; T1 is the depth (nm) at the location where the atomic ratio x / y of oxygen to carbon is 2 when component analysis is performed by SIMS in the thickness direction from the second surface to the first surface.
[0057] When Txy is within the expected range, the adhesion between the base layer and the first inorganic layer is controlled so that interlayer peeling does not occur, the foldability and surface hardness are excellent, the scratch resistance is improved, and it can be more appropriately used as a protective film for foldable display devices. On the contrary, if Txy exceeds the expected range, some components may be driven to one side of the surface, resulting in poor durability of the film.
[0058] In addition, if Figure 5 As shown, the contents of carbon and oxygen may increase or decrease in a certain ratio, respectively, according to the depth of the first inorganic layer.
[0059] For example, the carbon C content can be reduced within a certain range of proportions from the second surface (outer surface) to the first surface (the bonding surface with the base layer). Specifically, when the composition analysis is performed by SIMS in the thickness direction from the second surface to the first surface of the first inorganic layer, the carbon content can be reduced by 4% to 8% compared with the carbon content of the second surface for every 10 nm increase in the measurement depth.
[0060] As another example, the carbon oxygen O content may increase within a certain range of proportions from the second surface (outer surface) to the first surface (bonding surface with the substrate layer). Specifically, when the composition is analyzed by SIMS in the thickness direction from the second surface to the first surface of the first inorganic layer, the oxygen content may increase by 4% to 8% compared with the oxygen content of the second surface for every 10 nm increase in the measurement depth.
[0061] The thickness of the first inorganic layer may be greater than 5 nm, greater than 10 nm, greater than 20 nm, greater than 30 nm, greater than 50 nm, or greater than 100 nm, or less than 1000 nm, less than 500 nm, less than 300 nm, less than 200 nm, or less than 150 nm. For example, the thickness of the first inorganic layer may be 10 nm to 500 nm.
[0062] Second inorganic layer
[0063] Figure 2 is a cross section of a film according to another embodiment.
[0064] refer to Figure 2 According to another embodiment, the film 10 further includes the first inorganic layer 210 and a second inorganic layer 220 , and the refractive index of the second inorganic layer 220 is different from that of the first inorganic layer 210 .
[0065] The refractive index of the second inorganic layer may be higher or lower than the refractive index of the first inorganic layer. Specifically, the refractive index of the second inorganic layer may be higher than the refractive index of the first inorganic layer.
[0066] The second inorganic layer may contain one or more inorganic components, for example, may contain one or more components selected from the group consisting of Li, Al, K, Ti, V, Cr, Mn, Co, Zn, Sr, Nb, Mo, In, Sn, Sb and Cs.
[0067] The inorganic component may be contained in the inorganic layer in the form of an oxide combined with oxygen. For example, the second inorganic layer may contain an inorganic substance in which one or more components selected from the group consisting of Li, Al, K, Ti, V, Cr, Mn, Co, Zn, Sr, Nb, Mo, In, Sn, Sb and Cs are combined with oxygen. Specifically, the second inorganic layer may contain an inorganic substance in which one or more components selected from the group consisting of Nb, Ti, Zn, Si, In, Sn and Cs are combined with oxygen; more specifically, the second inorganic layer may contain an inorganic substance selected from the group consisting of niobium oxide (NbO, NbO2, Nb2O5), zinc oxide (ZnO), titanium oxide (TiO2) and indium tin oxide (ITO).
[0068] The thickness of the second inorganic layer may be greater than 5 nm, greater than 10 nm, greater than 20 nm, greater than 30 nm, greater than 50 nm, or greater than 100 nm, or less than 1000 nm, less than 500 nm, less than 300 nm, less than 200 nm, or less than 150 nm. For example, the thickness of the second inorganic layer may be 10 nm to 500 nm.
[0069] The thin film according to the above embodiment includes one or more first inorganic layers and second inorganic layers, respectively, and the first inorganic layers and second inorganic layers can be arranged alternately with each other. Therefore, the anti-reflection function can be imparted by the refractive index combination of these inorganic layers.
[0070] For example, the lamination configuration of the film is exemplified as follows:
[0071] Base layer / first inorganic layer / second inorganic layer;
[0072] Base layer / first inorganic layer / second inorganic layer / first inorganic layer;
[0073] base layer / first inorganic layer / second inorganic layer / first inorganic layer / second inorganic layer / first inorganic layer; and
[0074] Base layer / first inorganic layer / second inorganic layer / first inorganic layer / second inorganic layer / first inorganic layer / second inorganic layer / first inorganic layer.
[0075] For example, the reflectivity of the film with the first inorganic layer and the second inorganic layer alternately arranged as described above can be 5% or less in all wavelength bands of visible light. Specifically, the reflectivity of the film in all visible light bands can be 4% or less, 3% or less, 2% or less, or 1% or less.
[0076] The first inorganic layer and the second inorganic layer may be formed by depositing respective inorganic substances, and thus the first inorganic layer and the second inorganic layer may be inorganic deposited layers.
[0077] The number of inorganic layers in the film may be 1, 2 or more, 3 or more, or 5 or more, specifically 1-10, 2-8 or 4-6.
[0078] Basal layer
[0079] The base layer plays a role of supporting the inorganic layer and is used as a substrate for depositing inorganic substances during the manufacturing process.
[0080] The substrate layer has flexibility to facilitate continuous roll-to-roll processing, and there is no particular limitation in terms of material. For example, the substrate layer may be a flexible polymer film.
[0081] The base layer may include a polymer resin. For example, the base layer may include one or more selected from the group consisting of polypropylene (PP), polyethylene (PE), polystyrene (PS), acrylate-butadiene-styrene copolymer (ABS), polycarbonate (PC), polyethylene oxide (POM), polyamide (PA), polyacrylamide (PPO), polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK), polystyrene sulfonamide (PPS), polyimide (PI), polyamide-imide (PAI) and polyethyleneamine (PEI).
[0082] The base layer may be a transparent film. For example, the visible light transmittance of the base layer may be greater than 85%, and specifically may be greater than 95%.
[0083] The thickness of the base layer may be 10 μm to 500 μm, specifically 10 μm to 200 μm, 20 μm to 100 μm, or 30 μm to 80 μm.
[0084] In addition, the film may form an adhesive layer on the other surface of the base layer (ie, on the other side of the surface where the first inorganic layer is formed). For example, the adhesive layer may include an optically transparent adhesive.
[0085] Characteristics and uses of thin films
[0086] The film according to the above-described embodiment has high light transmittance and excellent scratch resistance, and thus is suitable for use as a window protective film for a display device.
[0087] The film according to the above embodiment may have a total light transmittance of more than 85%. For example, the light transmittance of the film may be more than 88%, or more than 90%, specifically, 85% to 99%, 90% to 99%, or 95% to 99%, but is not limited thereto.
[0088] In addition, the film may have a pencil hardness of 4H or more or 5H or more measured under a load of 500 g and 0.5 mm / sec according to JIS-5400. The pencil hardness measurement may be performed on the opposite surface of the substrate layer in the film, that is, on the first inorganic layer (or the second inorganic layer).
[0089] In addition, the film according to the above embodiment has excellent adhesion between the base layer and the inorganic layer and folding durability, so it can be used as a protective film in flexible display devices, specifically suitable for windows of foldable display devices, and can maintain excellent performance even after repeated folding and use.
[0090] For example, after the film is immersed in hot water at 100°C for 30 minutes, the cross-cut test result performed according to ISO 2409 standard can be 100 / 90 or more (i.e., no peeling or delamination occurs in more than 90 of 100 lattice units), and specifically can be 100 / 95 or more, or 100 / 97 or more.
[0091] In addition, the film is cut into a size of 15 cm in length and 2.54 cm in width, and the folding test is repeated at a speed of once every 2 seconds at room temperature to fold the base layer inwardly and make the curvature radius 2R until interlayer peeling or cracking occurs, and the number of foldings can reach more than 40,000 times. For example, the number of foldings can reach more than 40,000 times, more than 60,000 times, or more than 80,000 times. Figure 6 An example of a folding test on a film sample. Figure 6 , fix the film sample 10a on the folding tester 3, and repeat folding at a constant folding speed (times / second) and curvature R to determine whether peeling or cracking occurs between the layers.
[0092] Film preparation method
[0093] The method for preparing a thin film according to an embodiment includes the step of depositing the first inorganic layer on one side surface of the substrate layer, wherein the first inorganic layer includes silicon oxycarbide SiO x C y .
[0094] The deposition may be performed by physical deposition. Specifically, the deposition may be performed by sputtering. More specifically, the deposition may be performed by reactive plasma sputtering. The plasma may be an arc discharge plasma or a glow discharge plasma.
[0095] Figure 3 A thin film preparation method according to an embodiment is provided.
[0096] refer to Figure 3 , the substrate 100 is mounted on the anode or ground electrode, the target 300 is mounted on the cathode electrode, and then the discharge gas 501 is injected while the discharge output power is applied. Thereafter, the discharge gas 501 is separated into a plasma 600 of ions and electrons. The ions of the discharge gas collide with the target 300 and sputter to separate the target, and the separated target material reacts with the reaction gas and is deposited on the surface of the substrate in the form of an oxide, or is deposited on the surface of the substrate in the absence of a reaction. The cathode electrode may be supplied with an AC power supply, in which case the target 300 may be divided into two parts (separated by a dotted line in the figure) and mounted on the cathode electrode.
[0097] In sputtering, silicon carbide (SiC) may be used as a target, oxygen may be used as a reaction gas, and argon, helium, neon or xenon may be used as a discharge gas. For example, the reaction gas may be injected at an amount of 5 sccm to 20 sccm, or an amount of 10 sccm to 15 sccm. In addition, the discharge gas may be injected at a flow rate of 200 sccm to 1000 sccm.
[0098] According to one embodiment, in the first inorganic layer, an oxygen content ratio and a carbon content ratio are changed in a thickness direction.
[0099] In the reactive plasma sputtering, while the base layer is continuously transported, the amounts of the reactive gas injected into a first position and a second position in the transport direction of the base layer may be adjusted to be different from each other.
[0100] refer to Figure 3 , by sputtering the target material 300 containing SiO x C yIn the process of depositing the first inorganic layer 210 on one side of the base layer 100, the discharge gas 501 reacting with the target material 300 and the first nozzle 401 and the second nozzle 402 spraying the reaction gas 502 are located on both sides of the deposition material 300 and are separated from each other. During the sputtering, the base layer 100 is transported to the site to be deposited on one side of the base layer 100 through the position opposite to the first nozzle 401 and the position opposite to the second nozzle 402 in sequence, and the flow rates of the reaction gas 502 sprayed from the first nozzle 401 and the second nozzle 402 can be adjusted to be different from each other.
[0101] Therefore, the particles deposited on the base layer 100 by the sputtering include high oxygen ratio particles 201, which are generated by the reaction of oxygen O2 as the reaction gas 502 with SiC released from the target material 300, and high carbon ratio particles 202, which do not react with the reaction gas. For example, the high oxygen ratio particles 201 and the high carbon ratio particles 202 can be deposited on one side of the base layer 100 at a position facing the first nozzle 401 and a position facing the second nozzle 402 in different proportions.
[0102] Specifically, the base layer is transported in the order of the first position and the second position, and the amount of the reaction gas injected into the first position may be greater than the amount of the reaction gas injected into the second position.
[0103] like Figure 3 As shown, the first nozzle 401 can spray the reaction gas 502 at a higher flow rate than the second nozzle 402. For example, the first nozzle can spray the reaction gas at a flow rate of 200 sccm to 400 sccm, and the second nozzle can spray the reaction gas at a flow rate of 0 sccm to 100 sccm. In this case, the particles 201 with a high oxygen ratio can be deposited at a position facing the first nozzle 401, and on the contrary, the particles 202 with a high carbon ratio can be deposited at a position facing the second nozzle 402.
[0104] refer to Figure 3 For example, the first nozzle 401 may spray the reaction gas 502, while the second nozzle 402 may not spray the reaction gas. In this case, the reaction gas 502 may be sprayed from the first nozzle 401 and diffused to the surroundings. That is, the reaction gas 502 may show the highest partial pressure at the position facing the first nozzle 401, and the partial pressure may gradually decrease as it moves away from the position facing the first nozzle 401. Therefore, the reaction between SiC separated from the target 300 and the reaction gas 502 may be most active at the position facing the first nozzle 401, and the reaction between SiC separated from the target 300 and the reaction gas 502 may occur least at the position facing the second nozzle 402.
[0105] Therefore, the deposition of the high oxygen ratio particles 201 produced by the reaction may be most active at the position facing the first nozzle 401 , and the deposition of the unreacted high carbon ratio particles 202 may be most active at the position facing the second nozzle 402 .
[0106] At this time, the base layer 100 is deposited in turn through the position opposite to the first nozzle 401 and the position opposite to the second nozzle 402, so that in the initial stage of deposition, the particles 201 with a high oxygen ratio are mainly deposited, and then as the deposition ratio of the particles with a high oxygen ratio gradually decreases, the deposition ratio of the particles 202 with a high carbon ratio gradually increases.
[0107] Therefore, the closer the deposited first inorganic layer 210 is to the base layer 100 in the thickness direction of the cross section, the higher the oxygen content ratio is. Conversely, the farther the first inorganic layer 210 is from the base layer 100 , the higher the carbon content ratio is.
[0108] The first inorganic layer may be deposited in two or more layers on the base layer, and the deposition may be performed two or more times. For this purpose, two or more identical targets may be sequentially arranged in a conveying path of the base layer for sputtering.
[0109] According to another embodiment, the method for preparing a thin film may further include the step of depositing a second inorganic layer on one side of the base layer, wherein the second inorganic layer has a different refractive index from the first inorganic layer. To this end, two target materials may be arranged in sequence in a conveying path of the base layer for sputtering.
[0110] One or more than two of the first inorganic layer and the second inorganic layer may be deposited respectively, and for this purpose, a target material may be prepared according to the type and number of inorganic layers to be deposited. For example, the inorganic target material used in the sputtering may be one or more than two, and may be one or more than two in total, and may specifically be 1 to 10, 2 to 8, or 4 to 6 in total.
[0111] For example, the method for preparing the thin film may be to alternately deposit the first inorganic layer and the second inorganic layer, and for this purpose, two target materials may be alternately placed on a conveying path of the substrate layer.
[0112] Therefore, the thin film can be prepared by a deposition method such as sputtering, and the substrate layer can be transported by a roll-to-roll process. The roll-to-roll process can efficiently prepare an inorganic multilayer thin film with continuity and uniform quality.
[0113] Figure 4 This is an example of a thin film preparation device using a roll-to-roll process. Figure 4 The base layer 100 can be unwound from the unwinding roller 720 and transported in a specific direction by the rotation of the roller 710, and the inorganic material is deposited by sputtering or the like and then wound into the winding roller 730.
[0114] As a specific example, an inorganic deposition apparatus using a roll-to-roll process may have five targets, namely a first target (310), a second target (320), a third target (330), a fourth target (340) and a fifth target (350); SiC may be used as the first target 310, the third target 330 and the fifth target 350, and a material selected from the group consisting of niobium oxide (NbO, NbO2, Nb2O5), zinc oxide (ZnO), titanium oxide (TiO2) and indium tin oxide (ITO) may be used as the second target 320 and the fourth target 340.
[0115] The thickness of the inorganic layer deposited from each of the targets by sputtering can be adjusted by changing the intensity of the power applied to the cathode electrode to which each target is mounted.
[0116] Display device
[0117] Figure 7 FIG. 1 is an exploded perspective view of a display device according to an embodiment. Figure 7 The display device 1 includes a display panel 30 ; a window 20 disposed on the front surface of the display panel 30 ; and a protective film 10 disposed on the surface of the window 20 .
[0118] The display panel 30 may be a liquid crystal display (LCD) panel. Alternatively, the display panel 30 may be an organic light emitting display (OLED) panel. The organic light emitting display device may include a front polarizing plate and an organic light emitting display panel. The front polarizing plate may be disposed on the front surface of the organic light emitting display panel. More specifically, the front polarizing plate may be adhered to the surface of the organic light emitting display panel displaying an image. The organic light emitting display panel displays an image in units of pixels by self-luminescence. The organic light emitting display panel includes an organic light emitting substrate and a driving substrate. The organic light emitting substrate includes a plurality of organic light emitting units corresponding to pixels, respectively. The organic light emitting units include a cathode, an electron transport layer, a light emitting layer, a hole transport layer, and an anode, respectively. The driving substrate is driven to be coupled to the organic light emitting substrate. That is, the driving substrate may be coupled so that a driving signal such as a driving current may be applied to the organic light emitting substrate. More specifically, the driving substrate may apply a current to each of the organic light emitting units to drive the organic light emitting substrate.
[0119] The thin film having the composition gradient inorganic layer according to an embodiment is used as the protective film 10 of the display device 1 .
[0120] That is, according to one embodiment, a display device includes a display panel; a window arranged on the front surface of the display panel; and a protective film arranged on the surface of the window; wherein the protective film includes a base layer; and a first inorganic layer arranged on one side surface of the base layer; the first inorganic layer includes silicon oxide carbon SiOxCy, and the oxygen content ratio and the carbon content ratio change in the thickness direction.
[0121] The display device according to one embodiment may be flexible. For example, the display device according to one embodiment may be a flexible display device, or may be a foldable display device. More specifically, the foldable display device may be an inward folding type or an outward folding type according to its folding direction.
[0122] Figure 8a and 8b They are external folding and internal folding flexible display devices. Figure 8b , the display device may be an inner folding flexible display device 1a, wherein the screen is located inside the folding direction thereof. Or, referring to Figure 8a , the display device may be an external folding flexible display device 1b, in which the screen is located outside the folding direction. Figure 8b In the case of the inner fold type 1a, the load is applied to the inward fold point p1, refer to Figure 8a In the case of the outer folding type 1b, the load is applied to the outward folded point p2. In this case, if the protective film 10 does not have sufficient interlayer adhesion or flexibility, the load during folding will cause interlayer peeling or cracking, which will deteriorate the characteristics.
[0123] However, since the display device according to the above embodiment uses a thin film having a composition gradient inorganic layer as a protective film, cracking or interlayer peeling does not occur even when repeatedly folded, and has high light transmittance and excellent scratch resistance, it is possible to protect the window. In addition, the protective film has an anti-reflection function, so the visibility of the device can be improved when used outdoors.
[0124] Implementation
[0125] The following embodiments are only for facilitating understanding, and the achievable scope is not limited thereto.
[0126] Comparative Example 1A. Preparation of substrate / SiC y Layered film
[0127] Prepare as Figure 3 A reactive plasma sputtering apparatus using a roll-to-roll method is shown. Figure 3SiC is used as a target material 300 and installed, argon Ar gas is used as a discharge gas and oxygen O2 is injected as a discharge gas. A polyethylene terephthalate film (PET, U483, Toray) with a thickness of 50 μm as the base layer 100 is transported in a roll-to-roll manner and passes in front of the first nozzle 401 and the second nozzle 402 in sequence.
[0128] When the vacuum degree reaches 5×10 -6 torr, after 3 hours of high vacuum pumping, as shown in Table 1 below, argon gas was sprayed at the same flow rate of 300 sccm at the first nozzle and the second nozzle without spraying oxygen for sputtering. As a result, a silicon carbide SiC layer with a thickness of about 150 nm was deposited on the base layer. y layer of film.
[0129] Comparative Example 1B. Preparation of substrate / SiC x Layered film
[0130] The same steps as in Comparative Example 1A were repeated, but Si was used as the target and installed, as shown in Table 1 below, and oxygen was sprayed at the same flow rate of 50 sccm at the first nozzle and the second nozzle for sputtering. As a result, a silicon oxide SiO layer with a thickness of about 150 nm was deposited on the base layer. x layer of film.
[0131] Comparative Example 1C. Preparation of substrate / SiO x C y Layered film
[0132] The same steps as those in Comparative Example 1A were repeated, but as shown in Table 1 below, oxygen was sprayed at the same flow rate of 25 sccm at both the first nozzle and the second nozzle for sputtering. As a result, a silicon oxycarbide SiO layer with a thickness of about 150 nm was deposited on the base layer. x C y layer of film.
[0133] Example 1. Preparation of substrate / SiO x C y Thin films composed of (composition gradient) layers
[0134] The same steps as those in Comparative Example 1A were repeated. As shown in Table 1 below, argon gas was sprayed at the same flow rate of 300 sccm at the first nozzle and the second nozzle, and oxygen was sprayed at a flow rate of 100 sccm only at the first nozzle, and sputtering was performed at the second nozzle without spraying. As a result, a silicon oxycarbide (SiO2) layer having a composition gradient in the thickness direction and a thickness of about 150 nm was deposited on the base layer. x C y ) film.
[0135]
Table 1
[0136]
[0137]
[0138] Comparative Example 2. Preparation of a thin film consisting of substrate / SiO2 / Nb2O5 / SiO2 / Nb2O5 / SiO2 layers
[0139] Prepare as Figure 4 A reactive plasma sputtering apparatus using a roll-to-roll method is shown. Figure 4 , Si as the first target 310, Nb as the second target 320, Si as the third target 330, Nb as the fourth target 340, and Si as the fifth target 350 are respectively installed around the roller 710 and arranged in sequence. These five targets are as follows Figure 3 As shown, a first nozzle and a second nozzle are provided to spray the discharge gas Ar and the reaction gas O2, respectively. A polyethylene terephthalate film (PET, U483, Toray) with a thickness of 50 μm as a base layer is transported in a roll-to-roll manner, and is passed in front of the first target, the second target, the third target, the fourth target, and the fifth target in sequence. After 3 hours of high vacuum pumping, when the vacuum degree reaches 5×10 - 6 torr, the first nozzle and the second nozzle of each target jetted the discharge gas Ar at a flow rate of 300 sccm and the reaction gas O2 at a flow rate of 50 sccm, and the power intensity was adjusted as shown in Table 2 below to adjust the thickness of the deposited inorganic layer. As a result, a laminated film with a total of five layers, in which silicon oxide SiO2 layers and niobium oxide Nb2O5 layers were alternately stacked on the base layer, was obtained.
[0140] Example 2. Preparation of substrate / SiO x C y (composition gradient) / Nb2O5 / SiO x C y (composition gradient) / Nb2O5 / SiO x C y Preparation of thin films with (compositionally gradient) layer composition
[0141] The same steps as those in Comparative Example 2 were repeated, except that the first target, the third target, and the fifth target were replaced with SiC, and the reactive gas O2 was sprayed only at the first nozzle in these targets, and the reactive gas O2 was not sprayed at the second nozzle, as shown in the aforementioned Example 1. In addition, the power intensity applied to each target was adjusted as shown in Table 2 below to adjust the thickness of the inorganic layer deposited thereby.
[0142] As a result, silicon oxycarbide SiO having a composition gradient in the thickness direction on the base layer is obtained.x C y A laminated film having a total of five layers, in which layers and niobium oxide Nb2O5 layers are alternately stacked.
[0143]
Table 2
[0144]
[0145]
[0146] Experimental Example 1: Measuring the composition gradient of the inorganic layer
[0147] In order to confirm the composition gradient, the composition of the thin film sample in the depth direction of the inorganic layer was measured by SIMS (Secondary Ion Mass Spectrometry), and the ratio of oxygen O and carbon C components was obtained. Specifically, based on the SIMS measurement values corresponding to silicon Si, oxygen O and carbon C, the stoichiometric atomic ratio of oxygen O and carbon C relative to silicon (Si) was calculated according to the depth of the inorganic layer, and the results are shown below Figure 5 .
[0148] Test Example 2: Total Light Transmittance
[0149] The total light transmittance of the film samples was measured using a transmission haze meter. The results are shown in Tables 3 and 4 below.
[0150] Test Example 3: Pencil Hardness
[0151] The pencil hardness of the inorganic layer surface of the film sample was measured under the conditions of 500 g load and 0.5 mm / sec in accordance with JIS-5400. The results are shown in Tables 3 and 4 below.
[0152] Test Example 4: Cross-cut test
[0153] After the film sample was immersed in hot water at 100° C. for 30 minutes, a cross-cut test was performed on the surface of the inorganic layer according to ISO 2409. The results are shown in Table 3 below.
[0154] Test Example 5: Folding Test
[0155] The film sample was cut into a length of 15 cm and a width of 2.54 cm, and mounted on a folding tester to confirm whether interlayer peeling occurred during repeated folding. The folding test folded the base layer inward and made its curvature radius 2R, and repeated the folding test up to 80,000 times at a speed of once every 2 seconds. As a result, if interlayer peeling and cracking were not observed in the film after repeated folding, it was determined to be OK, and if interlayer peeling or cracking was observed, it was determined to be NG. The results are shown in Tables 3 and 4 below.
[0156]
Table 3
[0157]
[0158] As shown in Table 3 above, the film with composition gradient according to Example 1 has high light transmittance and excellent scratch resistance, interlayer adhesion and folding durability. In contrast, the films without composition gradient of Comparative Examples 1A to 1C have poor evaluation results for at least one of the above characteristics.
[0159]
Table 4
[0160]
[0161] As shown in Table 4 above, the film of Example 2 having a composition gradient has excellent anti-reflection function, and at the same time, compared with the film of Comparative Example 2 without a composition gradient, has excellent scratch resistance and folding durability.
Claims
1. A film comprising: basal layer, and A first inorganic layer, wherein the first inorganic layer is disposed on one side surface of the base layer; The first inorganic layer comprises silicon oxycarbide SiO x C y , and the oxygen content ratio and carbon content ratio change in the thickness direction The first inorganic layer has a first surface facing the base layer, and a second surface opposite to the first surface; As the oxygen content ratio gradually decreases from the first surface to the second surface, the carbon content ratio gradually increases. The film has a Txy of 40% to 60% defined by the following formula: Txy(%)=[(T0-T1) / T0]×100 in, T0 is the thickness of the first inorganic layer, in nm; T1 is the depth (nm) of a point where the atomic ratio x / y of oxygen to carbon is measured to be 2 when component analysis is performed by SIMS in the thickness direction from the second surface to the first surface.
2. The film according to claim 1, characterized in that In the first surface, the atomic ratio of oxygen O:carbon C is 1.5-1.9:0.1-0.5, and in the second surface, the atomic ratio of oxygen O:carbon C is 0.05-0.1:0.8-0.
9.
3. The thin film as described in claim 1, when the composition is analyzed by SIMS in the thickness direction from the second surface to the first surface of the first inorganic layer, as the measurement depth increases by 10nm, the carbon content decreases by 4% to 8% compared with the carbon content of the above-mentioned second surface.
4. The film according to claim 1, characterized in that The film is cut into a size of 15 cm in length and 2.54 cm in width. Under normal temperature conditions, the folding test is repeated at a speed of once every 2 seconds so that the base layer is folded inwardly and the curvature radius is 2R until interlayer peeling or cracking occurs. At this time, the folding number reaches more than 40,000 times and the total light transmittance is more than 85%; According to JIS-5400 standard, the pencil hardness measured under the conditions of 500g load and 0.5mm / sec is 4H or more; After soaking in hot water at 100°C for 30 minutes, the cross-cut test result according to ISO 2409 standard is above 100 / 95.
5. The film according to claim 1, characterized in that The film further comprises a second inorganic layer having a different refractive index than the first inorganic layer; The second inorganic layer comprises an inorganic substance in which one or more components selected from the group consisting of Li, Al, K, Ti, V, Cr, Mn, Co, Zn, Sr, Nb, Mo, In, Sn, Sb and Cs are combined with oxygen; The thickness of each of the first inorganic layer and the second inorganic layer is 10 nm to 500 nm; The first inorganic layer and the second inorganic layer are arranged alternately with each other; Wherein, the reflectivity of the film is less than 5%.
6. A method for preparing a thin film as claimed in claim 1, comprising the step of depositing the first inorganic layer on one side surface of the substrate layer, wherein the first inorganic layer comprises silicon oxycarbide SiO x C y ; In the first inorganic layer, the oxygen content ratio and the carbon content ratio are caused to vary in the thickness direction.
7. The method for preparing a thin film according to claim 6, characterized in that: The deposition is performed by reactive plasma sputtering; Silicon carbide SiC is used as the target; The reaction gas uses oxygen, and the discharge gas uses argon, helium, neon or xenon; In the reactive plasma sputtering, while the base layer is continuously transported, the amounts of the reactive gas injected into a first position and a second position in the transport direction of the base layer are adjusted to be different from each other.
8. A display device, characterized in that: Include: Display panel; A window disposed on the front surface of the display panel; and A protective film disposed on the surface of the window; Wherein, the protective film comprises: basal layer; and A first inorganic layer disposed on one surface of the substrate layer; The first inorganic layer comprises silicon oxycarbide SiO x C y , and the oxygen content ratio and carbon content ratio change in the thickness direction, The first inorganic layer has a first surface facing the base layer, and a second surface opposite to the first surface; As the oxygen content ratio gradually decreases from the first surface to the second surface, the carbon content ratio gradually increases. The protective film has 40% to 60% of Txy defined by the following formula: Txy(%)=[(T0-T1) / T0]×100 Wherein, T0 is the thickness of the first inorganic layer, in nm; T1 is the depth (nm) of a point where the atomic ratio x / y of oxygen to carbon is measured to be 2 when component analysis is performed by SIMS in the thickness direction from the second surface to the first surface.